IMPLEMENTASI KEBIJAKAN SUPERVISI PENDIDIKAN DI MADRASAH IBTIDAIYAH KANTOR KEMENTRIAN AGAMA KABUPATEN CIAMIS - Mia Helmia (Jurnal Pendidikan Sang Surya, 2024)
The implementation of learning supervision policies often faces various challenges, limited resources, lack of supervisor competence, and weak teacher participation. This results in less than optimal education quality. The implementation of effective supervision policies is expected to encourage teachers to continue to develop their competence, thereby realizing quality learning. This study uses a qualitative approach and descriptive methods at MI Ciamis Regency. This study produces: as key factors determining the success of the implementation of learning supervision policies in improving the quality of education, including: effective, consistent and continuous implementation design, effective communication in the implementation of learning supervision policies; the support and commitment of leaders in the implementation of learning supervision policies; increasing capacity and resources as the main key to achieving the effectiveness of the implementation of learning supervision policies and realizing improvements in the quality of education; participation and involvement of stakeholders in the implementation of learning supervision policies in improving the quality of education; and evaluation of the implementation of learning supervision policies in improving the quality of education is needed.